1958
DOI: 10.1152/ajplegacy.1958.192.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Recovery Induced by Bacterial Endotoxin in Irradiated Mice

Abstract: Mice given an intraperitoneal injection of Salmonella typhosa endotoxin 24 hours before irradiation showed an advance in the recovery of granulocytes, platelets and hemoglobin, with the effect on lymphocyte counts relatively small. Differences in bone marrow cellularity and in ability to mobilize granulocytes were particularly striking. Effects of an injection given after irradiation although significant were less pronounced. The induction of hemopoiesis is thought to be responsible for the increase in surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1962
1962
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…From these results the authors concluded that the effects of LPS were not dependent on interactions with primary radiation reaction products or that irradiation destroyed the ability of the rodent to respond to LPS. In a follow up paper (Smith et al 1958) the authors reported that recovery of granulocytes, platelets and hemoglobin were improved in mice injected with LPS 24 hours before lethal total body irradiation. LPS given to mice one hour after whole thorax irradiation revealed mitigating effects on lung injury (Zaidi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…From these results the authors concluded that the effects of LPS were not dependent on interactions with primary radiation reaction products or that irradiation destroyed the ability of the rodent to respond to LPS. In a follow up paper (Smith et al 1958) the authors reported that recovery of granulocytes, platelets and hemoglobin were improved in mice injected with LPS 24 hours before lethal total body irradiation. LPS given to mice one hour after whole thorax irradiation revealed mitigating effects on lung injury (Zaidi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of haemopoietic recovery after sub-lethal irradiation of endotoxin-treated mice has been well documented (Smith et al, 1958a(Smith et al, , b, 1959Hanks & Ainsworth, 1967b). The present studies were done with the purpose of getting some information about the mode of recovery.…”
Section: Haemopoietic Recovery In Endotoxin-treated Mice After Irradimentioning
confidence: 89%
“…Endotoxin injection either before or after irradiation was found to hasten endogenous recovery of haemopoiesis in mice (Smith, Alderman & Gillespie, 1958a;Smith, Marston & Cornfield, 1959;Hanks & Ainsworth, 1967a). Also, endotoxin treatment of recipient mice after cell transplantation enhanced the spleen colony forming ability of injected CFU (Gidtili, Fehbr & Vhrterbsz, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Windle (27). Recent studies have presented evidence that an increase in mitotic activity of all granulocyte precursor elements occurred after stimulation with pyrogen (28).…”
Section: Methodsmentioning
confidence: 99%